2011
DOI: 10.1124/mol.111.074013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity in CB2 Cannabinoid Receptor Signaling and Regulation: Implications for the Therapeutic Potential of CB2 Ligands

Abstract: Receptor internalization increases the flexibility and scope of G protein-coupled receptor (GPCR) signaling. CB 1 and CB 2 cannabinoid receptors undergo internalization after sustained exposure to agonists. However, it is not known whether different agonists internalize CB 2 to different extents. Because CB 2 is a promising therapeutic target, understanding its trafficking in response to different agonists is necessary for a complete understanding of its biology. Here we profile a number of cannabinoid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
149
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 52 publications
11
149
6
2
Order By: Relevance
“…Although initial experiments failed to detect functional coupling of CB 2 receptors to G protein-gated inwardly rectifying potassium channels and calcium channels (Felder et al, 1995;Pertwee, 1997), other reports suggest that CB 2 receptors can modulate the activity of these channels (Ho et al, 1999;McAllister et al, 1999;Atwood et al, 2012b). Atwood et al (2012b) showed CB 2 receptor-mediated inhibition of voltagegated calcium channels in AtT20 cells.…”
Section: Ion Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although initial experiments failed to detect functional coupling of CB 2 receptors to G protein-gated inwardly rectifying potassium channels and calcium channels (Felder et al, 1995;Pertwee, 1997), other reports suggest that CB 2 receptors can modulate the activity of these channels (Ho et al, 1999;McAllister et al, 1999;Atwood et al, 2012b). Atwood et al (2012b) showed CB 2 receptor-mediated inhibition of voltagegated calcium channels in AtT20 cells.…”
Section: Ion Channelsmentioning
confidence: 99%
“…Thus, the reason some of the earlier studies failed to find ion channel modulation can likely be attributed to the functional selectivity of the ligands used in the earliest studies (see below) (Atwood et al, 2012b).…”
Section: Ion Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim of these studies was to synthesize compounds with high specificity for the second cannabinoid receptor (CB2), transmitting antiinflammatory effects and pain release [35][36][37] . However, these efforts resulted in a large number of structurally different drug candidates that exhibited undesirable psychoactive effects [38][39][40] due to their binding affinity to the first cannabinoid receptor (CB1).…”
Section: The Evolution Of Synthetic Cannabinoidsmentioning
confidence: 99%